Preparation and Catalytic Study of Mn-NaX, Cu-NaX and Ag-/AgNPs-NaX Zeolites - Borislav Barbov; Katerina Zaharieva; Petya Karakashkova; Hristo Penchev; Liliya Tsvetanova; Silvia Dimova (Engineering Proceedings, 2023)
FAU-type zeolite NaX was successfully prepared using hydrothermal synthesis at 90 °C for 6 h. The Mn- and Cu-ion-exchanged NaX zeolites were obtained. After the ion exchange, the zeolite powders were thermally treated at 300 °C. As well as Ag-ion-exchanged zeolite, NaX and zeolite were impregnated with two types of Ag nanoparticle dispersions: citrate surface-stabilized (Cit@Ag NPs) and polymer-stabilized (PVP@Ag) nanoparticles. Silver nanoparticles were synthesized using the electrochemical reduction method. The changes in the phase and chemical composition and structure of the obtained zeolite powders before and after ion exchange or impregnation were investigated by PXRD analysis, FTIR spectroscopy, and XRF analysis. The results show that Mn, Cu-exchanged NaX, and that impregnated with Ag demonstrated catalytic abilities towards ozone decomposition in comparison with pure zeolite (non-catalytic activity).